Diversidade étnico-cultural no currículo: ações para formação de professores realizadas por dois Núcleos de Estudos Afro-Brasileiros paulistas (2003 - 2013) - Camargo, Rosana Maria de (2015)
The current research investigates the actions and the preparation of teaching materials for teacher training of the two Centers of São Paulo Afro-Brazilian Studies during the period from 2003 to 2013, in concordance to legislation 10.639/03. The objective of this research is to identify the tendencies (thematic/conceptual/methodological) that guide the production of these materials. The inclusion in the school syllabus of the ethnic and cultural diversity topic is analysed in the educational materials with a theoretical frame of reference from Goodson and Popkewitz. The hypothesis presented is that the prevalence of a racial democracy myth, together with the school curricular policy in the specific period and the actions and productions of the mentioned centers, have projected the promotion of racial equality policies and given teachers the opportunity to have a critical comprehension of the historical, political and cultural dimensions concerning the inclusion of this topic in the school materials. However, evidence from the analyses conducted in this research show that little has changed in the pedagogical methods